Basalt powder as an eco-friendly filler for epoxy composites: Thermal and thermo-mechanical properties assessment. (1st May 2019) - Matykiewicz, Danuta; Barczewski, Mateusz; Michałowski, Sławomir
Abstract: The aim of this study was to assess the influence of basalt powder on the thermo-mechanical properties of epoxy composites. The thermal stability was investigated through thermogravimetric analysis, flammability UL-94 test, and microcalorimetry. The degradation of the composite materials was evaluated using Kissinger's and Ozawa's methods. Moreover, the thermo-mechanical properties of the composites were determined through dynamic mechanical thermal analysis. Hardness was investigated with Shore D durometer. The results proved that basalt powder can be successfully used as an eco-friendly modifier for the epoxy resin. The thermo-mechanical properties of the composites improved with increased contents of this mineral filler. The presence of basalt powder retarded the degradation rate of the epoxy matrix as consequence the values of energy activation Ea for modified epoxy materials and total heat release THR were higher than for the reference sample. Moreover, the addition of basalt powder improved stiffness and hardness of the composites.